Polymorphism study in barley (Hordeum vulgare) genotypes using microsatellite (SSR) markers (Bangladesh Journal of Agricultural Research, 2014)
The experiment was conducted at the Molecular Breeding Lab of Plant Breeding Division, Bangladesh Agricultural Research Institute (BARl) to assess the inter and intra species diversity within the barley genotypes. Ten barley genotypes were used for polymorphism study through SSR markers. Among them, six markers showed distinct polymorphism within the barley genotypes. It was observed that the genotypes BB-1 and BB-3 were more diverged (0.255) compared to other genotypes. On the other hand, the genotypes BB-2, P-33, P-19, and P-25 were very much similar in their genetic level (83.00%) followed by BB-2, BB-4, BHL-19, P-19, BHL-18, BB-5, P-19, P-25, and P-33 (78.70%). The two dimensional graphical view of Principal Coordinate Analysis (PCO) showed the spatial distribution of the 10 barley genotypes along the two principal axes. The genotypes viz., BB-1 and BB-3 were found far away from centroid of the cluster and rest of the genotypes were placed around the centroid (Fig. 8). The genotypes that placed far away from the centriod were more genetically diverged compared to the genotypes placed near the centriod which were likely to be genetically more similar. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20078 Bangladesh J. Agril. Res. 39(1): 33-45, March 2014